2015
DOI: 10.1080/02508060.2015.1050580
|View full text |Cite
|
Sign up to set email alerts
|

Firms’ willingness to invest in a water fund to improve water-related ecosystem services in the Lake Naivasha basin, Kenya

Abstract: A valuation scenario was designed using a contingent-valuation approach and presented to decision makers in business firms in Kenya's Lake Naivasha basin to test how applicable a water fund might be as a potential financing mechanism for a payment for water-related ecosystem services scheme. The findings indicate that measuring a firm's willingness to invest in ecosystem services could help determine whether a firm would invest and engage with other stakeholders to pool their investments in ecosystem services.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…In the relevant literature, other determinants of willingness to invest in private businesses are the a manufacturer's reputation and the trust in a manufacturer's credibility, whereas supplier dependence and trust in a manufacturer's benevolence are not reported as significant, especially in the retail marketplace of the Asian economy [12,13].…”
Section: Willingness To Invest In Renewable Energy Sources (Res) Infrmentioning
confidence: 99%
“…In the relevant literature, other determinants of willingness to invest in private businesses are the a manufacturer's reputation and the trust in a manufacturer's credibility, whereas supplier dependence and trust in a manufacturer's benevolence are not reported as significant, especially in the retail marketplace of the Asian economy [12,13].…”
Section: Willingness To Invest In Renewable Energy Sources (Res) Infrmentioning
confidence: 99%
“…1) is a fragile (and degraded) endorheic lake ecosystem supporting a rich variety of flora and fauna [11,57]. Economic developments in the area are strongly connected to the lake ecosystem and the hydrological processes in the Lake Naivasha basin (3400 km 2 ; [34,37]). The upstream part of the Lake Naivasha basin comprises the Gilgil, Malewa, and Turasha sub-basins (Fig.…”
Section: The Lake Naivasha Basinmentioning
confidence: 99%
“…To companies this could be valuable if the enhancement of social services improves their relationship with communities and the government in their region. In this respect, it is of interest that studies on willingness to pay (e.g., [24]) revealed that companies would not invest in a water fund primarily for reasons of financial benefits, but rather were motivated to contribute to the common good. This suggests that a purely financial model may not be appropriate to fully explain decision-making by firms interacting with landscapes.…”
Section: Motives For Engagementmentioning
confidence: 99%
“…Koellner et al [32] found a demand for carbon sequestration among international firms, whereas Costa Rican firms were interested in watershed protection, biodiversity conservation, carbon sequestration and scenic beauty (in this order of preference). Mulatu et al [24] investigated the willingness to invest in a water fund for managing the landscape for ecosystem services, as an alternative governance arrangement to direct payments. Companies differed in the interest they expressed for landscape services: for example, carbon sequestration was mainly of interest to energy companies, while improving water quality and landscape beauty were prioritized by large-scale farms.…”
Section: Examples From the Scientific Literaturementioning
confidence: 99%
See 1 more Smart Citation